2014
DOI: 10.1039/c4ra05981f
|View full text |Cite
|
Sign up to set email alerts
|

Highly stereoselective one-pot construction of trisubstituted tetrahydro-β-carboline-fused diketopiperazines: a synthetic route towards cialis analogues

Abstract: A facile and efficient synthetic method for the stereoselective preparation of trisubstituted tetrahydro-β-carboline-fused diketopiperazine derivatives is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The synthesised CDPs were subjected to PAMPA model assay to evaluate the passive BBB transport ability. [18] These experimental results revealed that most of the CDPs have the potential to cross the PAMPA, as evaluated over a duration of 4 h. Among all, Oct-N-MePhe (39.4 %), Cha-N-MePhe (35.1 %), 2Nal-N-MePhe (33.7 %), HomoPhe-N-MePhe (26.8 %) and Phe-N-MePhe (20.8 %) have shown the best transportation across BBB over 4 h in PAMPA assay (Figure 8A, [38][39][40][41][42]. These values are similar or better than some of the known drugs such as carbamazepine and propranolol.…”
Section: Biological Barrier Shuttles Cargo Encapsulation and Delivery And Drug Detection 41 Synthetic Cdps As Bbb Shuttlesmentioning
confidence: 96%
“…The synthesised CDPs were subjected to PAMPA model assay to evaluate the passive BBB transport ability. [18] These experimental results revealed that most of the CDPs have the potential to cross the PAMPA, as evaluated over a duration of 4 h. Among all, Oct-N-MePhe (39.4 %), Cha-N-MePhe (35.1 %), 2Nal-N-MePhe (33.7 %), HomoPhe-N-MePhe (26.8 %) and Phe-N-MePhe (20.8 %) have shown the best transportation across BBB over 4 h in PAMPA assay (Figure 8A, [38][39][40][41][42]. These values are similar or better than some of the known drugs such as carbamazepine and propranolol.…”
Section: Biological Barrier Shuttles Cargo Encapsulation and Delivery And Drug Detection 41 Synthetic Cdps As Bbb Shuttlesmentioning
confidence: 96%
“…[136] The β-carboline scaffold is also present in numerous active pharmaceuticals including the anti-malarial cipargamin, anti-cancer lurbinectedin and the erectile dysfunction drug tadalafil. [135,[137][138][139][140] Currently, numerous strategies have been outlined for the enantioselective Pictet-Spengler reaction including organo-and transition-metal catalysis. [141,142] However, it was over half a century after the discovery of the chemical transformation before an enzyme catalysed Pictet-Spengler reaction was reported.…”
Section: Biocatalytic Pictet-spengler Reactionsmentioning
confidence: 99%
“…Jida et al. reported a Ugi‐multicomponent reaction coupled with Pictet‐Spengler reaction strategy for the synthesis of diversely subsituted library of tetrahydro‐β‐carboline fused diketopiperazines (Scheme ) . Synthesis started with a Ugi multicomponent reaction of N 2 ‐Boc‐ L ‐tryptophan primary amines 309 , formaldehyde and tert ‐butylcyanide in methanol to obtain a dipeptide framework.…”
Section: β‐Carboline Fused Heterocycles Synthesized Via Post‐pictet‐smentioning
confidence: 99%